Building an advocacy model to improve the dementia‐capability of health plans in California. Issue 12 (2nd September 2021) - Hollister, Brooke A.; Yeh, Jarmin; Ross, Leslie; Schlesinger, Jennifer; Cherry, Debra
Abstract: Background: Given the high and growing prevalence of Alzheimer's disease and related dementias, and the intensity of this population's care needs, it is imperative that healthcare systems increase their capacity to effectively serve people living with dementia (PLwD). The Dementia Cal MediConnect (Dementia CMC) project proposes an advocacy model that may foster dementia‐capable systems change. Methods: The Dementia CMC project was a 5‐year partnership (2013–2018) between local Alzheimer's organizations and 10 managed care health plans (HPs) in California's duals demonstration. It used an advocacy model with the following steps: (1) Identify dementia‐capable best practices to set as systems change indicators; (2) Identify and leverage public policies in support of systems change indicators; (3) Identify and engage champions; (4) Develop and advocate for a business case to improve dementia care; (5) Identify gaps in dementia‐capable practices; (6) Provide technical assistance, tools, and staff training to address the gaps in dementia‐capable practices; and (7) Track systems change. Systems change data were collected through participant observation with HPs and interviews with key informants representing partnering organizations or government entities. Results: Participating HPs reported making systems changes toward more dementia‐capable practices such as: better pathways for detection and diagnosis; better identification, assessment, support, and engagement of caregivers; and improved systems of referral to community‐based organizations (CBOs), including Alzheimer's CBOs. Some indicators of systems change were inconclusive due to flawed assumptions around HP's care coordination, and the availability of common electronic health records between HPs and providers. Conclusion: The application of this advocacy model in California has led to systems changes that can improve care for PLwD and their caregivers and should be replicated to expand the dementia‐capability of other health systems. Continued efforts to refine indicators are needed to capture systems change in complex and changing health systems. Abstract : See related Editorial by Callahan et al .